Correlation between echographic gastric emptying and appetite: influence of psyllium. Issue 8 (August 1992) - Bergmann, J F; Chassany, O; Petit, A; Triki, R; Caulin, C; Segrestaa, J M
Abstract : The correlation between ultrasonographic gastric emptying and appetite was studied. Echographic evaluation of gastric emptying by measurement of the antral vertical diameter and assessment of sensations of hunger and satiety using analogue visual scales were performed simultaneously in 12 healthy volunteers. Measurements were carried out after the intake of 10.8 g psyllium or placebo in a randomised, crossover, double blind trial. The correlation between echographic gastric emptying and sensations of hunger and satiety was excellent (p < 0.001) after the intake of either psyllium or placebo. Psyllium significantly delayed gastric emptying from the third hour after a meal. It increased the sensation of satiety and decreased hunger at the sixth hour after the meal. The association between echographic measurement and visual scales is a simple method of evaluating the relationship between the stomach and appetite. The pharmacodynamic effect of psyllium should be confirmed by longterm therapeutic trials.